2018
DOI: 10.1098/rsbl.2018.0532
|View full text |Cite
|
Sign up to set email alerts
|

Learning from others: an invasive lizard uses social information from both conspecifics and heterospecifics

Abstract: Species that are able to solve novel problems through social learning from either a conspecific or a heterospecific may gain a significant advantage in new environments. We tested the ability of a highly successful invasive species, the Italian wall lizard Podarcis sicula , to solve a novel foraging task when social information was available from both a conspecific and an unfamiliar heterospecific ( Podarcis bocagei ). We found that Italian wall lizards that had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 17 publications
1
35
0
Order By: Relevance
“…Shifts in behavior most likely follow after experience with a certain situation allowing the individual to learn an appropriate response. Animals might innovate solutions to problems by modifying existing behavior, come up with new behaviors, or learn socially from conspecifics or even native congeneric heterospecifics (Wright et al, 2010;Damas-Moreira et al, 2018). Cognitive ability can play an important role during the different stages of the invasion process, but which abilities increase invasion success within or across stages?…”
Section: Cognitive Abilities That Can Increase Invasion Successmentioning
confidence: 99%
See 1 more Smart Citation
“…Shifts in behavior most likely follow after experience with a certain situation allowing the individual to learn an appropriate response. Animals might innovate solutions to problems by modifying existing behavior, come up with new behaviors, or learn socially from conspecifics or even native congeneric heterospecifics (Wright et al, 2010;Damas-Moreira et al, 2018). Cognitive ability can play an important role during the different stages of the invasion process, but which abilities increase invasion success within or across stages?…”
Section: Cognitive Abilities That Can Increase Invasion Successmentioning
confidence: 99%
“…When no demonstrators were present or water was added instead of the food odor, observers did not change their behavior showing that their behavior was guided by that of the demonstrators irrespective of whether demonstrators were conspecifics or heterospecifics (Camacho-Cervantes et al, 2015). Furthermore, a recent study showed that invasive Italian wall lizards, Podarcis sicula, readily learn stimuli associated with a food reward (in an artificial foraging task using differently colored food wells) from both conspecifics and heterospecifics and made fewer errors when learning socially as opposed to individually (Damas-Moreira et al, 2018). Social learning has, however, limitations.…”
Section: Social Learning and The Spread Of Knowledgementioning
confidence: 99%
“…Some individuals (n = 18) either did not attempt to feed on both feeders in AM or, more commonly, PM during training, or did not make any foraging attempts during a final test session and were removed from further analyses. Following previous learning studies [27][28][29], we also established a training criterion. As we are interested in whether time-dependent memories are formed and can therefore guide behaviour in the absence of the reward, we identified individuals that correctly adjust their behaviour in AM and PM sessions during training with reinforced feeders.…”
Section: (B) Training Criterionmentioning
confidence: 99%
“…Moreover, spatial learning proficiency did not predict lid opening ability in water skinks (Qi et al, 2018). Finally, Italian wall lizards (Podarcis sicula) and a closely related species P. bocagei learnt the same lid-opening technique (Damas-Moreira et al, 2018).…”
Section: Lizardsmentioning
confidence: 87%
“…Eight different studies have used training procedures to teach lizards to remove lids from wells for a reward and although training preceded the tasks, these are examples of reptile species solving novel problems (Clark et al, 2014;Damas-Moreira et al, 2018;Leal, & Powell, 2012;Noble et al, 2014;Powell, 2012;Qi et al, 2018;Riley et al, 2018;. Only two studies attempted to test a reptile on a puzzle box task.…”
Section: Lizardsmentioning
confidence: 99%